Stoning Law in The Perspective of Islamic Law: A Comparison of The Implementation of Stoning Law in Indonesia and Arab Countries - Rijal, Ahlan Khoir Syah; Rohmah, Siti Ngainnur; Akmal, Najmuddin; Putri, Amelia Fajri; Fitri, Anisa (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2025)
This study explores the contextual interpretation of Islamic law within the framework of Arab countries and Indonesia, emphasizing the historical, social, and political factors that influence their legal systems. It highlights the complexities of implementing Islamic law, particularly concerning human rights and international legal standards. The research critiques the role of monarchies in Arab countries, where legal systems often reflect a blend of traditional Islamic principles and modern secular influences. The study also discusses the challenges these legal systems face in balancing religious mandates with contemporary human rights issues, as highlighted by various international organizations. The findings indicate that while Islamic law provides a fundamental legal framework, its application is significantly shaped by the socio-political context of each Arab country, leading to diverse interpretations and implementations of justice. This study concludes by advocating for a more nuanced understanding of Islamic law that considers both its religious roots and the modern legal landscape.Keywords: Islamic Law; Arab Countries; Human Rights; Legal System; International Law; Socio-Political Context